A Qualitative Exploration of Sport and Social Pressures on Elite Athletes in Relation to Disordered Eating - Stoyel, Hannah; Delderfield, Russell; Shanmuganathan-Felton, Vaithehy; Stoyel, Alex; Serpell, Lucy (Frontiers in Psychology, 2021)
Introduction. Athletes are at increased risk of disordered eating compared to non-athletes. Inspired by an investigation into Petrie and Greenleaf (2007) and Stoyel and colleagues’ (2020) etiological model of disordered eating in athletes, the current study aimed to explore a problematic aspect of the model: athletes’ lived experiences of social and sport pressures in relation to the onset of disordered eating and differing eating behaviors. Methods. Nine (N=9) male and female athletes representing a range of endurance sports took part in semi-structured interviews. Thematic analysis was utilized. Analysis. Analysis revealed two main themes each with two corresponding subthemes (1) Conflating physical appearance and sporting ability with the subthemes of (1a) social comparison in a sporting world and (1b) societal notions of ‘the athlete body’ and (2) Living as an athlete with the corresponding subthemes of (2a) discipline and sacrifice and (2b) the balancing act. Discussion. It is the complex interaction between societal expectations as lived out in social messages and comparisons, and sport pressures that contributes to the development of disordered eating behaviors. These findings suggest that prevention and treatment of disordered eating in athletes can be applied from those already established in nonsporting realm.